Characterization of hazelnut oil extracted by ultrasound assisted solvent extraction - Geow, Chin Hong; Tan, Mei Ching; Chin, Nyuk Ling (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this study, ultrasound treatment was used to enhance the oil yield of hazelnut oil. The oil was extracted by using hexane with 15 min ultrasound treatment initially. Ultrasound amplitude (30, 60 and 90%), solvent to solid ratio (6:1, 8:1 and 10:1 mL/g) and extraction temperatures (28, 38 and 48°C) gave positive effect on oil yield. Higher oil yield of 88.78% was achieved at highest settings of ultrasound amplitude, solvent to solid ratio and temperature as compared to 69.57% obtained from the lowest settings of those parameters. Characterization of extracted oil in terms of iodine value, acid value, and peroxide value were carried out in this study. The results showed that ultrasound treatment would not significantly (p>0.10) affect those values. All the values obtained were in the range of acceptable levels for edible oil. In term of fatty acid, gas chromatograph analysis results showed that around 9% of saturated and 91% of unsaturated fatty acids were observed in hazelnut oil for all the amplitudes applied. More crack structures were observed on the surface of hazelnut samples after ultrasound treatment under scanning electron microscopy images, which could enhance the oil yield. This concluded that extraction with ultrasound aid could be used as an alternative extraction method for hazelnut oil with no negative impact on oil quality.